A Genealogy of Refusal: Walking Away from Crisis and Scarcity Narratives - Meyers, Natalie K.; Martinez-Montavon, Anna Michelle; Narlock, Mikala; Stathers, Kim (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2021)
Why can’t librarians “Just Say No”? To answer this question, we look at workplace refusal through the fine arts, literature, and popular culture to construct a genealogy of workplace refusal. In it, we also begin to trace a lineage of crisis narrative critique alongside the library profession’s inheritance of vocational awe. We explore the librarian’s role and voice through the lens of both popular culture and academic publications. In our companion multimedia, hypertextual Scalar project also titled A Genealogy of Refusal: Walking Away from Crisis and Scarcity Narratives, we contextualize strategies of refusal in libraries through critical response to and annotations of film clips and illustrations. We examine gender differences in portrayals of workplace refusal. We laugh when in Parks and Recreation a stereotypical librarian ignores a stripper but warns noisy patrons: “Shh—This is a library!” We are horrified when aspiring librarians in Morgenstern’s Starless Sea, hands tied behind their backs, have their tongues torn from their mouths. Elinguation as a job prerequisite? No, thanks. The implications of saying “No” are many. We explicate ways librarians are made vulnerable by crisis narratives and constructed scarcity. We advocate for asset framing and developing fluencies in hearing and saying “No.” Looking forward, how long will it take librarians to reclaim “Yes” in a way that works for us?